The different fate of the Siza’s SAAL housing in Porto - Fernandes, Eduardo (2018)
The SAAL (Ambulatory Service of Local Support) was a national housing program created by Nuno Portas, Secretary of State of Housing and Urban Development, in June 1974 (only two months after the Portuguese revolution). It was a paradigmatic experience of Portuguese architecture, which implied an idea of participation of the future dwellers in the design decisions. From the point of view of architectural theory, the two works that Álvaro Siza designed in Porto in the context of the SAAL process (which contributed in a decisive way to the internationalization of his career) are a perfect case study of the processes of reuse / rehabilitation of modern buildings. Being two very different situations, both in their conception assumptions and in the recent rehabilitation processes that affected them, these works can allow students to problematize several issues, from different points of view. In the initial design, both the interventions were based on the idea of considering the traditional proletarian housing (the so-called ‘island’) as a formal model, while improving it with new meaning, dignity and comfort. Siza aimed to preserve the community qualities of this ancient housing scheme, but also its typological structure. However, while in S. Victor, the ‘new island’ appears in its traditional place, the interior of the block, invisible from the city, in Bouça, the SAAL housing disrupts the urban fabric and seeks to show itself to the city, proclaiming a new urban order that simultaneously rejects the traditional morphology of the urban space and the ‘Athens Charter’ doctrine. There are different lessons that can be learned from these cases in the subject of reuse: in Bouça, the recent rehabilitation and expansion process allowed Siza to complete his vision for the site, offering the city a neighborhood with a true inter-class community spirit; at the same time, the S. Vitor area was affected by a municipal intervention that demolished the preexisting walls which framed the SAAL housing, creating an open public space which expose the decay problems that affect the building. The paper will present a pedagogical approach, considering the good results of the rehabilitation process in Bouça as a counterpoint to the analysis of the current situation of S. Vitor, speculating on the way to intervene in a context were the answers are neither obvious nor easy.